Many Mansions Lessons of Faith, Family, and Public Service - Boyer, Kathryn (Abilene Christian University Press, 2014)
Kathryn T. Boyer, the wife of Ernest L. Boyer (1928-1995), offers a window into the life she shared with her prominent husband and the constant balancing act they faced in relation to their faith, family, and public service. Often cited but seldom understood, Ernest L. Boyer (1928-1995) was one of the most influential voices in education in the latter-half of the twentieth century. The reports he wrote while heading the Carnegie Foundation for the Advancement of teaching influenced the way we view students from pre-school through college. This heart-warming memoir of the life offers an inside look into what truly defined him. Having moved approximately twenty times over the course of their lives together, Kathryn details with winsome yet honest prose the challenges and joys that came with the balancing act of faith, family, and public service. Those indebted to Ernest Boyer's legacy will find this work indispensable reading.